Creation and validation of an elderly patient referral flowchart for no geriatric practitioner use (Research, Society and Development, 2021)
The world population has been undergoing changes in the social, political and technological spheres, characterizing the demographic transition, which changed the age pyramid, aging at a faster rate than the birth. These changes had an impact on health care. Thus, the objective was to create and validate a flowchart for the criterion of elderly patients for use by no geriatric doctor. This research included three stages. The first be composed of an analytical cross-sectional study, using a self-administered questionnaire for 49 no geriatrics practitioners, which assessed the doctor's level of knowledge regarding the correct referral; the second, in the creation of the Flowchart to guide general practitioners to the correct referral to the elderly health clinic; and, in the third stage, a questionnaire was conducted with specialist physicians to validate the flowchart created. With the investigation of 44 questionnaires, 65.9% of professionals referred an elderly person at some point in their career. It was shown that 43.2% of the participants got 4 questions right, having more knowledge about the cognitive disability syndrome and less about postural instability. A referral flowchart for guidance was developed and validated by expert opinion with 84.4% approval. Established of the results obtained, the implementation of the flowchart standardized and contributed to a more accurate, quick and efficient clinical decision, for the purpose of make more efficient the meeting of the requests of the elderly health clinic and increase the numeral of vacancies for the protection of the elderly who actually need specialized care.